In vivo recordings in freely behaving mice using independent silicon probes targeting multiple brain regions - Ferreira-Fernandes, Emanuel; Laranjo, Mariana; Reis, Tiago; Canijo, Bárbara; Ferreira, Pedro A.; Martins, Pedro; Vilarinho, João; Tavakoli, Mahmoud; Kunicki, Carolina; Peça, João (Frontiers in Neural Circuits, 2023)
In vivo recordings in freely behaving animals are crucial to understand the neuronal circuit basis of behavior. Although current multi-channel silicon probes provide unparalleled sampling density, the study of interacting neuronal populations requires the implantation of multiple probes across different regions of the brain. Ideally, these probes should be independently adjustable, to maximize the yield, and recoverable, to mitigate costs. In this work, we describe the implementation of a miniaturized 3D-printed headgear system for chronic in vivo recordings in mice using independently movable silicon probes targeting multiple brain regions. We successfully demonstrated the performance of the headgear by simultaneously recording the neuronal activity in the prelimbic cortex and dorsal hippocampus. The system proved to be sturdy, ensuring high-quality stable recordings and permitted reuse of the silicon probes, with no observable interference in mouse innate behaviors.